2018
DOI: 10.1002/uog.20104
|View full text |Cite
|
Sign up to set email alerts
|

Screening for morbidly adherent placenta in early pregnancy

Abstract: Accurate prediction of MAP can be achieved by ultrasound examination at 12-16 weeks' gestation. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 49 publications
(72 reference statements)
1
70
0
2
Order By: Relevance
“…A recently published assessment of a two‐stage screening and diagnostic protocol for CSP also demonstrated high accuracy for sonographic prediction of PAS in the first trimester (false‐positive rate of 0.1%); in that study, all cases of PAS were associated, at the time of diagnostic assessment as early as 12 weeks in a PAS‐specialized clinic, with the sonographic features: intraplacental lacunae, retroplacental arterial‐trophoblastic blood flow and irregular placental vascularization on three‐dimensional power Doppler. These two studies describe ‘classic’ ultrasound findings identified in the late first to early second trimesters for accurately characterizing PAS.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A recently published assessment of a two‐stage screening and diagnostic protocol for CSP also demonstrated high accuracy for sonographic prediction of PAS in the first trimester (false‐positive rate of 0.1%); in that study, all cases of PAS were associated, at the time of diagnostic assessment as early as 12 weeks in a PAS‐specialized clinic, with the sonographic features: intraplacental lacunae, retroplacental arterial‐trophoblastic blood flow and irregular placental vascularization on three‐dimensional power Doppler. These two studies describe ‘classic’ ultrasound findings identified in the late first to early second trimesters for accurately characterizing PAS.…”
Section: Introductionmentioning
confidence: 82%
“…However, several studies have illustrated that low anterior sac position within the niche (or on the hysterotomy scar), thin (or no) myometrial thickness, early appearance of placental lacunae and hypervascularity at the uterus–bladder interface are the most reliable sonographic features at 11–14 weeks associated with subsequent diagnosis of PAS. A recently published assessment of a two‐stage screening and diagnostic protocol for CSP also demonstrated high accuracy for sonographic prediction of PAS in the first trimester (false‐positive rate of 0.1%); in that study, all cases of PAS were associated, at the time of diagnostic assessment as early as 12 weeks in a PAS‐specialized clinic, with the sonographic features: intraplacental lacunae, retroplacental arterial‐trophoblastic blood flow and irregular placental vascularization on three‐dimensional power Doppler. These two studies describe ‘classic’ ultrasound findings identified in the late first to early second trimesters for accurately characterizing PAS.…”
Section: Introductionmentioning
confidence: 87%
“…Panaiotova et al . reported that accurate prediction of AIP can be achieved by assessment of the presence of six ultrasound markers, including intraplacental lacunar spaces and non‐visible CS scar, at 12–16 weeks' gestation. Therefore, screening for AIP in early pregnancy is recommended.…”
Section: Pathophysiology Of Cspmentioning
confidence: 99%
“…Ultrasound signs of AIP can also be used to describe CSP, as the two conditions share common histopathological features and CSP seems to be a precursor of AIP 15 (Figure 1). Panaiotova et al reported that accurate prediction of AIP can be achieved by assessment of the presence of six ultrasound markers, including intraplacental lacunar spaces and non-visible CS scar, at 12-16 weeks' gestation 16 . Therefore, screening for AIP in early pregnancy is recommended.…”
Section: Diagnosis Of Csp and Aipmentioning
confidence: 99%
“…High‐frequency transducers and SMI offer significant clinical benefits for obstetricians, allowing delineation of histological structures and hemodynamics of minute vessels of the placenta. Compared with conventional ultrasound, sonohistological evaluation using this high‐resolution probe has the potential to improve the accuracy of ultrasound evaluation of PAS and could facilitate its diagnosis at earlier gestations since it can depict small lesions. Accurate prenatal diagnosis of PAS and planned treatment in centers with surgical expertise should help improve the outcome of women with PAS.…”
mentioning
confidence: 99%